Turning off inflammation naturally via dual antioxidant and anti-inflammatory actions of chestnut wood extract through PPARγ and NF-κB pathways - Dylan Lambert; Mathys Buisine; Muriel Billamboz; Samir Jawhara (PLoS ONE, 2026)
Background Inflammatory bowel disease (IBD) arises from a persistent imbalance between oxidative stress and immune homeostasis, driving tissue injury and chronic intestinal inflammation. Natural polyphenols are increasingly recognized as powerful modulators of redox and immune pathways, yet the bioactivity of complex, tannin-rich extracts remains largely overlooked. Among these, chestnut wood extract (CWE) particularly rich in highly soluble tannins, represents a valuable yet underexplored reservoir of bioactive molecules. This study aimed to characterize the phytochemical diversity of CWE and evaluate its anti-inflammatory, antioxidant, and epithelial-protective properties. Methods and Results Through a comparative screening of polyphenol-enriched plant extracts, chestnut wood extract (CWE) emerged as a standout candidate displaying potent anti-inflammatory and antioxidant effects. Phytochemical profiling revealed 23 distinct phenolic constituents, including phenolic acids, gallotannins, ellagitannins (castalagin, vescalagin), roburins, and ellagic diglucosides, highlighting its high chemical diversity. Functionally, CWE strongly attenuated NF-κB activation and reduced pro-inflammatory cytokines (IL-6, IL-1β, TNF-α) in human macrophages and Caco-2 intestinal epithelial cells. It also mitigated oxidative stress by reducing intracellular ROS and upregulating key antioxidant enzymes (SOD-1, GPX-1, catalase), while restoring mitochondrial membrane potential. Mechanistically, CWE enhanced PPARγ expression and behaved as a selective PPARγ modulator, synergizing with rosiglitazone and controlling IL-6 via both PPARγ-dependent and -independent pathways. Remarkably, CWE preserved intestinal epithelial barrier integrity and boosted Claudin-1 expression under inflammatory challenge. In vivo, CWE improved Caenorhabditis elegans survival following Candida albicans infection, supporting its protective capacity against oxidative and pathogenic challenges. Conclusion Collectively, these findings unveil CWE as a chemically rich, biologically active plant extract with dual antioxidant and anti-inflammatory properties. By restoring redox balance, modulating PPARγ signaling, and preserving epithelial integrity, CWE represents a promising natural candidate for mitigating intestinal inflammation.